2006
DOI: 10.2135/cropsci2005.0185
|View full text |Cite
|
Sign up to set email alerts
|

Grazing Research in the Humid East: A Historical Perspective

Abstract: A historical perspective of the major developments in grazing research for the humid Eastern USA was addressed. Consideration was given to the emergence of the area of grazing research relative to the initial structure of agricultural institutions, the orientation of scientist within the constraints of the institutional boundaries (departments) and the carry-through noted today. Early grazing research was constrained to the informal literature and discussed as informational, demonstrational, and experimental. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 78 publications
(79 reference statements)
1
15
0
Order By: Relevance
“…The TMR system allowed feed ingredients to be blended together and providing the blend was mixed thoroughly enough to prevent separation and sorting, cows consumed a nutritionally balanced diet in every bite. Following this trend, the average milk production per cow increased from about 3200 kg in 1960 to 8890 kg in 2005(National Agricultural Statistics Service, 2006.…”
Section: The Use Of Pasture In High-producing Dairy Cow Feeding Systementioning
confidence: 99%
See 1 more Smart Citation
“…The TMR system allowed feed ingredients to be blended together and providing the blend was mixed thoroughly enough to prevent separation and sorting, cows consumed a nutritionally balanced diet in every bite. Following this trend, the average milk production per cow increased from about 3200 kg in 1960 to 8890 kg in 2005(National Agricultural Statistics Service, 2006.…”
Section: The Use Of Pasture In High-producing Dairy Cow Feeding Systementioning
confidence: 99%
“…The findings from the first replicated grazing trials using lactating dairy cows, however, were not published until the mid 50s (Seath et al, 1956;Lassiter et al, 1956;both articles cited by Burns, 2005). Seath et al (1956), from the University of Kentucky, Lexington, reported total digestible nutrients (TDN) yield per surface unit, milk production persistency, and body weight changes for lactating dairy cows.…”
Section: Dairy Grazing Research In Eastern Usmentioning
confidence: 99%
“…Thus, as a function of assessing individual and combined components of plants and animals, scientists representing 2 or more disciplines within a university or with other research institutions are collaborating to meet common objectives. A research structure of funding, direction, and accountability must overlay disciplinary "boundary lines" and bring together scientists with a common goal and vision (Burns, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The lack of public funding for sustained programs of sufficient size and depth to realistically conduct whole systems research is a significant constraint. These are the same constraints cited by Burns (2006) related to grazing research in the humid eastern USA. Multidisciplinary teams supported by the USDA in cooperation with land grant universities will be critical to advancements in our understanding of integrated croplivestock systems and how to manage them for the good of society.…”
Section: Constraints To Adoption and Research Needsmentioning
confidence: 60%